Which leadership model holds well in emergency medicine? (A comparison between three types of leadership models). - Mustafa Y. Alhinai (Saudi Journal of Emergency Medicine)
For a healthcare system to be successful, doctors must be competent and leaders must be effective. The healthcare industry is often characterized by the presence of teams. In order to be a good team leader, one must possess certain attributes, which are often found in emergency physicians. Three leadership models are discussed in this report: the transactional, the transformational, and the situational leadership models. The situational leadership appears to be the most appropriate leadership approach for an emergency medicine scenario. Within the concept of situational leadership, there is not a single approach that is applicable to every situation and every circumstance. Therefore, it is extremely important for team leaders to explore the capabilities of the team members, determine the intrinsic motivators of each individual, and work towards ensuring that the team members are fully engaged [SJEMed 2023; 4(3.000): 177-180]